Computational fluid dynamic analysis at dam spillway due to different gate openings - Zawawi M.H.; Aziz N.A.; Radzi M.R.M.; Hassan N.H.; Ramli M.Z.; Zahari N.M.; Abbas M.A.; Saleha A.; Salwa A.; Muda Z.C. (American Institute of Physics Inc., 2023)
This paper presents a case study of dam where computational fluid dynamic (CFD) modelling is applied to simulate the three-dimensional (3D) flow hydraulics using computational aided program using ANSYS in order to analyse the existing fluid dynamic from reservoir to spillway of the dam due to long exposure to high pressure of water and high velocity of discharge. The purpose of this study is to ensure efficiency, reliability and safety of the dam generally and specifically on the spillway. Based on the findings, a model that have a worst condition based on both analysis is a model that have bigger area of the opening gate. This is because of the huge amount of the water release from the upstream to the downstream and produce a high value of water velocity and high impact from the water that fall from upstream towards the dam spillway. In order to avoid any sudden huge amount of the water release, the water level of the reservoir need to be check frequently. The water release from the dam need to be control to avoid any disaster to the environment and the dam structure. 2018 Author(s).